Analisis Kepuasan Pelanggan Atas Kualitas Produk dan Pelayanan Dengan Metode SEM-PLS - Besse Arnawisuda Ningsi (Program Studi Statistika FMIPA UNJ, 2018)
This study aims to analyze what factors can affect customer satisfaction and to estimate customer satisfaction models for Bleached Cotton products. Respondents in this study were Bleached Cotton customers. The variables used consist of customer satisfaction variables (Y) as dependent variables and independent variables namely product quality (X1) and service quality (X2) with each variable will be measured by the indicator. The sample in the study was taken as simple as 33 people. The instrument used in this study as a means of collecting virgin using questionnaires / questionnaires. This questionnaire is used to measure the customer satisfaction index. Statements are prepared using a Likert scale with five respondents' answers to customer satisfaction, namely: Strongly Agree (SS), Agree (S), Doubt (RR), Disagree (TS) and Strongly Disagree (STS). The data analysis technique used is Partial Least Square-Strutural Equation Modeling (PLS-SEM) which is used to predict and develop theories. Based on the results of the analysis, it was found that product quality has an effect on customer satisfaction, which means that not all customers will feel satisfied if only with the quality of the product, but there must be other factors. In this study the most positive indicators of production quality so that customer satisfaction can be achieved are performance indicators. While indicators that are less influential on the quality of production causing customer satisfaction to be achieved are indicators of design. Service quality has an effect on customer satisfaction, which means that the higher and better the quality of service provided, it can ensure customer satisfaction can be achieved. The first positive most influential indicator of service quality so that customer satisfaction can be achieved is the assurance indicator. And indicators that are less influential on the quality of production so that customer satisfaction is not achieved is an indicator of empathy. Product quality and customer service can simultaneously influence customer satisfaction so that if these two variables are prioritized, customer satisfaction will be achieved more optimally. Product quality and customer service are measured using indicators of design, performance, conformance, tangiable, emphaty, responsiveness, reliability, assurance are factors that influence customer satisfaction because when viewed from the output obtained.